An Analysis On Professional Workers Permit System In Indonesia As A Barrier To Trade In Services - Teuku Akbar Lazuardi; Wardah Wardah (Jurnal Ilmiah Mahasiswa Bidang Hukum Kenegaraan, 2018)
As the members of The World Trade Organization (WTO) Indonesia has the duty to implement the General Agreement on Trade in Services (GATS). The Indonesia regulation toward foreign professional workers permits system need to be consistent with GATS regulations. The arrangement of the entry permit of the professional foreign worker in Indonesia must be consistent with rules of the GATS, to work in Indonesia the workers from other WTO members must have a visa and work permit (IMTA) as regulated in article 34 point d law no 6 of 2011 concerning about immigration regulation the limited stay permit visa regulation for foreign professional workers and law no 13 of 2003 concerning about labor regulation. But in principle, the rules are considered less consistent in undergoing specific rules of commitment set in the GATS. According to the GATS, States should regulated rules that do not burden other members. And also regulates the national regulation on foreign professional workers same like local workers which is not considered as barrier in trade in services. This article aims to see the visa regulation system and the IMTA that applicable to professional workers who intend to work in Indonesia is consistent with the rules that governed by the WTO. This research uses normative empirical research. The data in this study were obtained through the library research to acquire secondary data in the form of studying the legislation, books, the internet and other scholarly works related to the problem of the research. Furthermore, fieldwork conducted for obtaining primary data by interviewing respondent and informant. The result of this article showed that the visa and IMTA regulation in Indonesia gives the negative effect on foreign professional workers. Indonesia action were done base on the law no 6 of 2011 concerning about immigration and the law no 13 of 2003 concerning about labor regulation. it is suggested that the government of indonesia produce  clearer regulation concerning the visa regulation and the IMTA in order to be better in managing the foreign professional workers. it need to be changed so it is not be considered as trade barriers in services.